The Balance of Aceh Development - Bidang Kajian Aparatur (Jurnal Transformasi Administrasi, 2013)
The development between districts and cities in Aceh has not spread evenly. Thus is the conclusion of Research Team of PKP2A IV LAN. Through written data analysis from Central Sta tistic Board (BPS) of Aceh Province, interviewbased research paper, and Focus Group Discussion(FGD)duringfieldstudyintenareas,foundthatunbalanceddevelopmentofAceh can be seen from the growth of PDRB value per capita and the growth of economy between unbalanced and unequal areas. It is caused by disparity of natural resources in each area, the production level in each area is not focus and irrelevant with local natural resources, and the concentration of labours are more relatively in developed areas. This research recommends that the Government need to formulate policies towards local expense that focus on local economy sources and integrated development cooperation between areas.